(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Polyolefin (linear low-density polyethylene, LLDPE) was blended with date palm wood (DPW) powder to prepare composites with concentrations of filler ranging from 10 to 70 wt.%. The Young´s modulus of the composites significantly increased with an increase in the filler content in the entire concentration range. The presence of the filler improved the flexural strength, which was represented by the flexural stress at peak. The water absorption test revealed that the composites had a strong tendency to absorb water, which was dependent on the filler content. The experimental data were compared with several theoretical models.